Utilization of Papaya As Raw Material for Solid Soap - Meidiana, Christia; Yudono, Adipandang; Firdausiyah, Nailah; Ari, Ismu Rini Dwi; Sari, Kartika Eka; Agustin, Imma Widyawati; Saragi, Sheren Regina Aurelia; Ta'ajuddin, Nauval Ali; Adhinianti, Ridzkika (TEKAD : Teknik Mengabdi, 2026)
In daily life, papayas are often discarded and become waste due to overripeness or not being consumed in time. Based on their composition, papayas have strong potential as a base for non-food products due to their wide-ranging benefits. Papain enzymes, vitamins A, C, and E, as well as flavonoids and saponins found in papaya, have been shown to possess antioxidant and antibacterial properties, and can act as natural exfoliating agents for the skin. These characteristics make papaya a promising natural ingredient for developing body care products such as bar soap. Accordingly, a Pengabdian kepada Masyarakat activity was carried out to introduce the use of papaya as a raw material for natural bar soap. This initiative aimed not only to address the issue of papaya waste but also to educate the community on the economic potential of household-level food processing. The activity was conducted through an educational and participatory approach, involving socialization and hands-on training. As a result, the program received positive responses and high enthusiasm from participants, and helped introduce new skills with potential for independent application and added household economic value.